2017
DOI: 10.1080/2000625x.2017.1367209
|View full text |Cite
|
Sign up to set email alerts
|

Nerve decompression and neuropathy complications in diabetes: Are attitudes discordant with evidence?

Abstract: External neurolysis of the nerve at fibro-osseous tunnels has been proprosed to treat or prevent signs, symptoms, and complications in the lower extremity of diabetes patients with sensorimotor polyneuropathy. Nerve decompression is justified in the presence of symptomatic compressed nerves in the several fibro-osseous tunnels of the extremities, which are known to be frequent in diabetes. Quite a body of literature has accumulated reporting results after such nerve decompression in the leg, describing pain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…29,42 Despite being still controversial, cumulative data suggest an important role for the peripheral nerve surgeon in identifying the patient at risk, with consequent treatment recommendations. 20,43,44 The positive effects of lower extremity nerve decompression surgery are underscored by other studies from different research groups, on various outcome parameters, 45,46 including sensibility tests, balance, pain, nerve conduction studies, tibial nerve ultrasound, and electromyographic recordings. Moreover, these studies suggest that lower extremity nerve decompression surgery is safe with respect to risk of surgical-site infection (5.9 percent versus 9.5 percent in other types of lower extremity surgery), and infections that do occur are usually straightforwardly treated.…”
Section: Discussionmentioning
confidence: 99%
“…29,42 Despite being still controversial, cumulative data suggest an important role for the peripheral nerve surgeon in identifying the patient at risk, with consequent treatment recommendations. 20,43,44 The positive effects of lower extremity nerve decompression surgery are underscored by other studies from different research groups, on various outcome parameters, 45,46 including sensibility tests, balance, pain, nerve conduction studies, tibial nerve ultrasound, and electromyographic recordings. Moreover, these studies suggest that lower extremity nerve decompression surgery is safe with respect to risk of surgical-site infection (5.9 percent versus 9.5 percent in other types of lower extremity surgery), and infections that do occur are usually straightforwardly treated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that nerves in the lower extremity of individuals with diabetes and sensorimotor polyneuropathy should be decompressed as a preventive procedure against “superimposed nerve entrapment”, with the intention to prevent diabetic foot ulcers [ 103 , 104 , 105 ]. The indications for such procedures have been questioned [ 106 ], but recent opinions have been raised that the scepticism concerning such a procedure should be reassessed [ 107 ]. To solve the question, standard definitions and outcome measures are used in prospective randomised controlled trials to determine the usefulness of such interventions [ 108 , 109 ].…”
Section: Controversies In Nerve Compression and Diabetesmentioning
confidence: 99%
“…7 Nickerson reviewed reports of the use of ND in DPN producing outcome improvements in pain relief, touch and vibratory sensibility, thermal sensation, perineural pressure, electrophysiologic EMG and NCV measures, pedal transcutaneous pO 2 , arterial flow pulsatility, balance, protection from initial DFU, lowest described ulcer recurrence risk and hospitalization for foot infections and amputation. 8 Since that review, further evidence has been published/addressing delayed mortality, prolonged survival without recurring ulceration, and improved intra-operative evoked motor potentials. 6,9 Animal models of induced diabetes with evolving sci- but recovery to nearly normal status by 3 months following ND.…”
mentioning
confidence: 99%
“…Daily plantar temperature monitoring can recognize incipient inflammation preceding skin breakdown and produce recurrences under 10% via activity restriction 15 . Nerve trunk decompression at fibro‐osseous tunnel entrapment sites was found by 4 authors to achieve DFU recurrence of <5% annually 8 . Hurdles to validating the surgical ND hypothesis are gathering the Level 1 evidence required to surmount scepticism, amending an incomplete aetiology thesis and treatment paradigm, training enough surgeons to safely treat hundreds of thousands of neuropathic DFU cases annually, and publishing cost‐benefit analysis based on the avoided expense of the next ulcer.…”
mentioning
confidence: 99%